Design and Driving Characteristics of a Bidirectional Micro-Device Based on Multi-Electrothermal Co-Actuation - Yujuan Tang; Zihao Guo; Yujiao Ding; Xinjie Wang (Micromachines)
In this paper, a bidirectional micro-device based on multi-electrothermal co-actuation is proposed for a fuze safety system, combining the advantages of the simple structure, small size, low input voltage, large output, and absence of electromagnetic interference in electrothermal actuators. Based on the working principle of the multi-electrothermal co-actuation device and the mathematical model of the single V-shaped electrothermal actuator established in this paper, the temperature distribution of the V-shaped electrothermal actuator is simulated. In addition, the dynamic response and the effect of geometric factors on the output performance of the multi-electrothermal co-actuation device are analyzed in detail. Furthermore, driving characteristics tests of the electrothermal micro-device are carried out. The experimental findings indicate that a displacement of approximately 258.95 μm with a response time of about 156.51 ms can be achieved by the V-shaped electrothermal actuator when the applied voltage is 1.2 V. In a single cycle, a total displacement of 340 μm is obtained by the co-actuation device in around 1.28 s.